HUMAN RESOURCE MANAGEMENT MODEL TO CREATE SUPERIOR PERFORMANCE - Yuniarsih, Tjutju; Sugiharto, Mochammad Dudih (UPI Press, 2016)
This research is motivated by the empirical conditions related to poor performance of human resources in various institutions in Indonesia. This research focuses on the uneven gains of competitive human resources due to workers’ characters which still prioritize routines and the fact that quality-oriented work culture has not been strongly established.. The solution offered is a model of human resource management that emphasizes the interaction between personal and situational factors that are directed at the creation of improved performance and productivity, as stated in behaviourist theory. Based on the above explanation, the aim of this second year research is to measure the effects of the two previously mentioned factors on performance. The research adopted quantitative approach with explanatory survey method. First year research was focused on an exploration with inductive approach to map the determining factors for variables that will build a model of human resource management in achieving superior performance. Second year research used explanatory survey, combining multiple regression analysis techniques to test the causal relation between variables, while the third year research will use Research and Development method to test the hyphothetical model. The subjects of this research were employees in educational institutions (Indonesia University of Education and Bandung State Polytechnic ), banks (West Java-Banten Bank and Indonesian People’s Bank), business institutions (Advent Hospital), and government institutions (Local Government Agencies in Bandung). The size of the samples was taken proportionally from each work unit by using proportionate random sampling. The number of units of analysis was 239 respondents determined by Solvin formula. The instruments of this research consisted of questionnaires, interview guide, and documentary study. The instruments were validated by expert judgment. The data were processed with the aid of SPSS version 21 and AMOS to find the causal relationship between variables, and regression analysis to identify variables forming superior performance. Based on the findings, it can be concluded that all personal aspects and situational aspects were proven to have significantly positive effects and contributions to create superior performance. The hypothetical model developed in this first and second year research will be tested in the next year’s research.